Does purchasing power mediate the marketing mix on purchasing decisions of IP publisher book customers - Latief Bayu Aji; Nur Achmad (Enrichment : Journal of Management, 2023)
Along with the times, the level of competition is getting higher and higher, including the operations of printing companies. In addition to competition between companies, printing companies have challenges in product adjustments that are no longer done offline printing, but also online. This research is aimed at analyzing the effect of the marketing mix on purchasing decisions with purchasing power as an intervening variable, the marketing mix studied as an independent variable, including, product, price, distribution and promotion. The research method uses a descriptive quantitative approach. The sample was determined as many as 103 IP Publisher consumers from June 2021 to July 2022 who were taken using the incidental sampling method. Data was collected using a questionnaire. The analysis tool uses SmartPLS. According to the analysis' findings, it is known: 1) there is a positive and significant effect between price on purchasing decisions, and purchasing power mediation strengthens the effect of price on purchasing decisions; 2) There is no effect between products on purchasing decisions, and purchasing power mediation weakens the effect of products on purchasing decisions; 3) there is a positive and significant effect between distribution on purchasing decisions, and purchasing power mediation weakens the effect of distribution on purchasing decisions; 4) There is no effect between promotions on purchasing decisions, and purchasing power mediation strengthens the effect of promotions on purchasing decisions.